ISSUES REGARDING THE JURISDICTION IN CASE OF JOINING THE CRIMINAL CASES - Dan LUPAȘCU; Mihai MAREȘ (Challenges of the Knowledge Society)
The joinder of criminal cases determines a prorogation of material or territorial jurisdiction of the court or, as the case may be, of the prosecuting authority ensuring a proper performance of the legal activities. The current Code of Criminal Procedure regulates both the compulsory joinder and the optional joinder of the criminal cases, according to a summary proceedings, stipulated in article 45 (during the trial), and, respectively, article 63 paragraph (1) related to article 45 (during the criminal investigation). The concurrence between the civil and military nature of the judicial body is settled in favour of the civil nature of the judicial body, observing the equivalence of its degree. After joining the cases, the enactment of certain decisions by the judicial body determines either maintaining the legal empowerment (in case of the court) or, as the case may be, declining the jurisdiction (in case of the prosecuting authority).